Perineal trauma after vaginal delivery in healthy pregnant women - Oliveira, Larissa Santos; Brito, Luiz Gustavo Oliveira; Quintana, Silvana Maria; Duarte, Geraldo; Marcolin, Alessandra Cristina (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Despite all the medical care provided during delivery labor, perineal injury is still prevalent and may lead to diverse pelvic floor disorders. The aim here was to investigate the prevalence of obstetric and anal sphincter injuries (OASIS) in healthy pregnant women after vaginal delivery. DESIGN AND SETTING: Cross-sectional study involving 3,034 patients with singletons in a secondary hospital for low-risk cases. METHODS: A standardized questionnaire was prepared and applied to medical files that had been completely filled out (classification of the Royal College of Obstetricians and Gynecologists, RCOG) in order to identify OASIS and analyze risk factors associated with mild and severe perineal lacerations. RESULTS: The women’s mean age was 25 years; more than half (54.4%) were primiparae. Almost 38% of the participants had perineal lacerations; these were severe in 0.9% of the cases. Previous vaginal delivery (odds ratio, OR: 1.64 [1.33-2.04]) and forceps delivery (OR: 2.04 [1.39-2.97]) were risk factors associated with mild perineal injuries (1st and 2nd OASIS classifications). Only remaining standing for prolonged periods during professional activity (OR: 2.85 [1.34-6.09]) was associated with severe perineal injuries. CONCLUSION: The prevalence of severe perineal injuries was concordant with data in the literature. The variable of standing position was considered to be a risk factor for severe perineal injury and should be further investigated.